PENGARUH KUALITAS INFORMASI, KUALITAS PRODUK DAN PERSEPSI RISIKO TERHADAP KEPERCAYAAN KONSUMEN DAN KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI KOTA PEKANBARU - Putra Eka Firmansyah; Restuti Sri; Jushermi Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of Information Quality, Product Quality andRisk Perception on Consumer Trust and Purchase Decisions at the ShopeeMarketplace in Pekanbaru City. The population in this study is all people whohave made purchases in the Shopee marketplace in Pekanbaru City. This studyconsists of five variables, including Information Quality (X1), Product Quality(X2), Risk Perception (X3), Consumer Trust (Y1) and Purchase Decision (Y2).The sample in this study amounted to 110 samples using the purposive samplingmethod. The analytical method in this study uses path analysis with dataprocessing using SPSS (Statistical Package of Social Science) version 16.0. Basedon the hypothesis test conducted, the research results show that InformationQuality has a positive and significant effect on Consumer Confidence andPurchase Decisions, Product Quality has a positive and significant effect onConsumer Confidence and Purchase Decisions, Risk Perception has a negativeand insignificant effect on Consumer Confidence but has a significant effect onPurchase Decision, Consumer Confidence has a positive and significant effect onPurchase Decisions and Consumer Confidence is not able to mediate theinfluence of Information Quality, Product Quality and Risk Perception onPurchase Decisions. Keywords: Information Quality, Product Quality, Risk Perception, ConsumerTrust, Purchase Decision